Aplikasi Terapi Wicara bagi Remaja Penyandang Disabilitas Intelektual Ringan - Thedy Yogasara; Cecilia Stefiany (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2019)
There are more than three million people in Indonesia who have speech disorders. Speech disorders are also experienced by people with intellectual disabilities, who need speech therapy to practice their expressive speech skills. However, the current types of speech therapy, in general, are not easily accessible and require considerable cost. The purpose of this study, therefore, is to provide a speech therapy tool that can be accessed easily and requires low cost. This research designs a mobile application as a speech therapy tool for teenagers with mild intellectual disability. The design process began with the identification of user needs, followed by the design of application concepts using a design workshop. The best concept was developed into a prototype, which was then evaluated through a usability testing, using effectiveness, efficiency, learnability, memorability, and accessibility as the evaluation criteria. Based on the evaluation, the effectiveness of the application is 82.2% and its efficiency is 78.9%. Meanwhile, the learnability and memorability of the application consecutively score 80% and 94.4%. These results show that the application has a good level of accessibility. Evaluation was also conducted using the System Usability Scale (SUS) questionnaire, which resulted in a total score of 74 (acceptable). In addition, interviews were conducted to identify remaining flaws that were subsequently used as a basis for design improvement of the application.